Parental Support Towards Quality Religious and Moral Education Delivery at Primary School Level - Annobil, Charles Nyarko; Annan, Abraham; Quansah, Samuel Douglas (Advances in Social Sciences Research Journal, 2020)
The nature and functions of the school reflect the demands and expectations of the larger society including parents. The objective of this sequential explanatory mixed method design study was to obtain the views of RME teachers and headteachers regarding how parents (of primary school pupils) were influencing quality delivery of Religious and Moral Education (RME) in Cape Coast, Ghana. Data were sought from 264 RME teachers and 15 headteachers through questionnaire, interview and lesson observation. The instruments were pre-tested and validated to obtain high degree of reliability and dependability. The questionnaire data obtained reliability co-efficient value of r =. 845, the observation data obtained Cohen’s Kappa value of .765 (k = .765, p < .000) and the interview data were duly validated to ensure interview trustworthiness. Frequencies, percentages, charts, tables, means and standard deviations were used to analyze the research questions while inferential statistics (multiple regression) was used to analyze the quantitative data. The research questions were discussed based on quantitative and qualitative analysis of the data collected. The variable (parent support) correlated averagely with r = 0.433, p = .000 with the teaching of RME at 5% significance level (α = .05); indicating that parental support has significant effect on quality delivery of RME (Teaching of RME) in the metropolis. It was found out that parents directly or indirectly contribute to RME instruction in the schools through counselling and material supports. Upon the findings it was recommended to parents to collaborate with RME teachers to ensure adequate provision of basic resources that can facilitate dispassionate and objective teaching and learning of RME.